(untitled) (Journal of Advanced Research in Social Sciences, 2021)
This article analyzed the KESBAN counterinsurgency model of Malaysia in combating the Communist Movement in 1989. It compare with the ongoing Nigerian government counterinsurgency against the Islamist Boko Haram group in the country. The empirical data gathered from secondary materials including both published and unpublished materials. The article revealed that the successes of the Malaysian combating the communist rebellion was influences by its KESBAN model premised on the heart and mind strategy in its campaign. It hence revealed that the protraction of the Boko Haram rebellion is promoted partly by the enemy-centered campaign of the government. The uses of excessive military force on fighters and implementing draconian laws targeting the host population bolstered the insurgent group. It enabled them accesses to logistics and intelligence thus influence the extension of its violence. As a panacea, the article suggest that Nigeria should borrow from Malaysia’s KESBAN model in its operation. On against the prevailing security only campaign, the government should adopt the Malaysia strategies of establishing new villages and raising of home guards to control the population. The Government should also focus on implementing economic empowerment programs for the resettled population.